A sesquiterpene quinone, dysidine, from the sponge Dysidea villosa, activates the insulin pathway through inhibition of PTPases - Zhang Yu; Li Yan; Guo Yue-wei; Jiang Hua-liang; Shen Xu (Acta Pharmacologica Sinica, 2016)
Aim: The sesquiterpene hydroquinones/quinones belong to one class of marine sponge metabolites, and they have received considerable attention due to their varied biological activities, including anti-tumor, anti-HIV, and anti-inflammatory action. In order to probe the potential anti-diabetic effect of the sesquiterpene hydroquinones/quinones, the effect of dysidine on the insulin pathway was studied. Methods: The promotion of glucose uptake by dysidine was studied in differentiated 3T3-L1 cells. The increase in membrane-located GLUT4 by dysidine was studied in CHO-K1/GLUT4 and 3T3-L1 cells by immuno-staining. The activation of the insulin signaling pathway by dysidine was probed by Western blotting. The inhibition of PTPases by dysidine was detected in vitro. Results: Dysidine, found in the Hainan sponge Dysidea villosa in the Chinese South Sea, effectively activated the insulin signaling pathway, greatly promoted glucose uptake in 3T3-L1 cells, and showed strong insulin-sensitizing activities. The potential targets of action for dysidine were probed, and the results indicated that dysidine exhibited its cellular effects through activation of the insulin pathway, possibly through the inhibition of protein tyrosine phosphatases, with more specific inhibition against protein tyrosine phosphatase 1B (PTP1B). Conclusion: Our findings are expected to expand understanding of the biological activities of sesquiterpene hydroquinones/quinones, and they show that dysidine could be a potential lead compound in the development of an alternative adjuvant in insulin therapy.